The La Bastida fortification: new light and new questions on Early Bronze Age societies in the western Mediterranean. (1st June 2014) - Lull, Vicente; Micó, Rafael; Rihuete-Herrada, Cristina; Risch, Roberto
Abstract : Recent excavations at La Bastida in south-eastern Spain have revealed an impressive stone-built fortification system dating to 2200–2100 cal BC that protected one of the main economic and political centres of Argaric Early Bronze Age society. It consists of parallel walls with projecting towers flanking a narrow entrance passage. The defensive character of these structures appears beyond question and their design suggests they were a response to significant changes in warfare and weaponry in this period. This sophisticated fortification system raises once again the question of possible Mediterranean contacts, along with social change and the role of physical violence in the rise of Argaric society.